2016
DOI: 10.1128/genomea.01003-16
|View full text |Cite
|
Sign up to set email alerts
|

Seven Bacteriophages Isolated from the Female Urinary Microbiota

Abstract: Recent research has debunked the myth that urine is sterile, having uncovered bacteria within the bladders of healthy individuals. However, the identity, diversity, and putative roles of bacteriophages in the bladder are unknown. We report the draft genome sequences of seven bacteriophages isolated from microbial communities from adult female bladders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 8 publications
0
27
0
Order By: Relevance
“…Several recent genomic sequencing based studies of human urine demonstrate that the urinary tract is not sterile even when urine cultures are negative; instead, the healthy urinary tract is host to a unique community of bacteria and viruses [2931]. The bladder microbiome of patients with asymptomatic bacteriuria is ecologically distinct from that of healthy patients with negative cultures [32].…”
Section: Epidemiology Microbiology and Pathogenesis Of Utismentioning
confidence: 99%
“…Several recent genomic sequencing based studies of human urine demonstrate that the urinary tract is not sterile even when urine cultures are negative; instead, the healthy urinary tract is host to a unique community of bacteria and viruses [2931]. The bladder microbiome of patients with asymptomatic bacteriuria is ecologically distinct from that of healthy patients with negative cultures [32].…”
Section: Epidemiology Microbiology and Pathogenesis Of Utismentioning
confidence: 99%
“…Coliphages in general are one of the most sequenced phage types with ~450 complete phage genomes within Genbank, isolated from a variety of sources including animal faeces (Niu et al, ; Smith et al, ; Sazinas et al, ; Golomidova et al, ), human faeces (Dalmasso et al, ), urine (Malki et al, ), river water (Alijošius et al, ), agricultural surface waters (Liao et al, ), lagoons (Ngazoa‐Kakou et al, ), sewage (Trotereau et al, ) and animal slurries (Sazinas et al, ). However, much less is known about the genetic diversity of coliphages in seawater.…”
Section: Introductionmentioning
confidence: 99%
“…While new urinary microbiome research has primarily focused on the bacterial constituents of this community (5), a few studies have shown that the urinary microbiota also includes viruses. First, viruses have been isolated from urine, including several eukaryotic viruses (15)(16)(17)(18)(19)(20)(21) and phages (22,23). Second, two metagenomic sequencing studies of the urinary virome (eukaryotic viruses and phages in the lytic cycle) have been conducted (24,25).…”
mentioning
confidence: 99%